Financial Performance Analysis Before and During The Covid-19 Pandemic - Ferina Nurlaily; Rahmat Alfiansyah Nasution (Politeknik Negeri Padang, 2021)
The trade sector is one of the biggest economic generators and the most contributing sector towards the gross domestic product (GDP). Unfortunately, the growth of the trade sector stumbles due to the Covid-19 pandemic. According to BPS, this sector is one of the real sectors that is greatly affected by the pandemic situation whereas the demand side experiences a big slump due to the lockdown which makes in and out goods hardly possible. Thus, it leads to the decline of export and import transactions. This study mainly attempts to investigate whether there are significant differences in financial performance during the Covid-19 pandemic and before in trading, service, and investment sector companies listed on the Indonesia Stock Exchange (IDX). Documentation study is implemented as a data collection technique with a quantitative comparative approach. Variables included in this study are Current Ratio (CR), Quick Ratio (QR), Cash Ratio (CR), Net Profit Margin (NPM), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Return on Equity (ROE), Return on Assets (ROA), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR). While the analytical technique used in testing the hypothesis is the Paired Sample T-Test and the Wilcoxon Sign Rank Test in the SPSS (Statistical Package for Social Science) program. Research finding shows significant differences in Net Profit Margin (NPM), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Return on Equity (ROE), and Return on Assets (ROA) before and during the Covid-19 pandemic. Keywords: Covid-19, Financial Performance, Liquidity Ratio, Profitability Ratio, Solvency Ratio, Indonesia